Freeing trade in North America - Anderson, Greg 1969- (Agenda Publishing Limited, 2020)
The North American idea -- What the NAFTA is (and is not) -- North America as region -- New ground broken and (mixed?) results -- Much ado about foreign direct investment -- Governance in the NAFTA, or lack thereof -- Labour and the environment -- NAFTA 2.0: did the USMCA modernize anything?
Literaturverzeichnis Seite 183-196
Keywords: Freihandelsabkommen; Nordamerika